Population pharmacokinetics and exposure–response of trilaciclib in extensive‐stage small cell lung cancer and triple‐negative breast cancer. Issue 3 (19th October 2022) - Li, Chao; Rich, Benjamin; Bullock, Julie M.; Barrière, Olivier; Marier, Jean‐Francois; Beelen, Andrew
Abstract : Aims: Trilaciclib is a first‐in‐class, intravenous cyclin‐dependent kinase 4/6 inhibitor that provides multilineage protection from chemotherapy‐induced myelosuppression. This analysis aimed to characterize the population pharmacokinetics (PK) of trilaciclib, identify potential covariates influencing trilaciclib PK, and evaluate exposure–response relationships in extensive‐stage small cell lung cancer (ES‐SCLC) and triple‐negative breast cancer (TNBC) trials. Methods: Population PK analysis was performed using data from healthy volunteers ( n = 72), patients with ES‐SCLC ( n = 111) and patients with TNBC ( n = 14). Exposure–response analyses were conducted to investigate the impact of trilaciclib exposure (AUC) on myeloprotective efficacy, antitumour efficacy and safety. Logistic regression and Cox regression models were used for binary and time‐to‐event endpoints, respectively. Results: Trilaciclib PK was described by a three‐compartment model. Sex, body surface area, baseline albumin concentration and age were identified as significant covariates on trilaciclib PK but did not have clinically relevant impact on exposure. Based on exposure–response analyses, lower and higher exposures of trilaciclib at clinical doses (200–280 mg/m 2 ) were associated with similar myeloprotective effects. Trilaciclib exposure did not impact the antitumour effects of chemotherapy. Higher exposure to trilaciclib was associated with higher probabilities of headache, phlebitis/thrombophlebitis and injection site reactions. Conclusion: No dose adjustments are required based on the covariates tested. Trilaciclib resulted in optimal myeloprotective effects with no impact on antitumour effects of chemotherapy. However, higher exposure increased the probabilities of adverse events. The data further support selection of the recommended phase 2 dose (trilaciclib 240 mg/m 2 ).